Data communication and computer networks - Tiwari, Bharat Bhushan; Agrawal, Rajneesh (New Delhi Vikas Publishing House, 2007)
Fundamentals of data communications ; Transmission media ; data modems ; multichannel data communications ; networking fundamentals ; data link protocols ; Local area networks ; Wide area networks ; Fiber optics communications ; wireless mobile communications